Management system of knowledge workers in the contemporary enterprise - Michal Igielski (Institute of Economic Research (IER), 2015)
Changes in the 21st century are happening more quickly, unexpectedly, not always in the way desired for the smooth functioning enterprises are turning up. It is domain of the globalization, where new events - chances or threats, cause challenges of the market, before which at present permanently all enterprises are being put. More and more he depends on immaterial resources of the enterprise which they constitute about his strategic potential. Companies form and are developing abilities, is exchanging them for competence which are becoming a base of their competitiveness. In this process he is becoming crucial conditioning, not that much what optimum, but competent managing the intellectual capital, of which meaning in the last period still is growing, and joint employing all organizational units is deciding on the market success. Some work demands a lot of the knowledge, of experience and the independent and custom thinking than other. It is essential for all employers in order to notice these differences creating the principle of the management new ketegoria of specialists, having a useful knowledge for functioning of the enterprise - with knowledge workers. Therefore an attempt to show the management system is a purpose of this article with knowledge workers in contemporary enterprises, based on conducted examinations, at turn 2013 and of 2014, in 100 large firms, acting in the area of the Baltic Sea Region.
Keywords: A11; D83; M12; O15; 330; knowledge worker; competitiveness; enterprise; management system